The neurophysiology of central and peripheral fatigue during sub-maximal lower limb isometric contractions - Berchicci, Marika; Menotti, Federica; Macaluso, Andrea; Di Russo, Francesco (Frontiers in Human Neuroscience, 2013)
Fatigue has been defined as an exercise-induced decline in force generation capacity because of changes at both the peripheral and central levels. Movement is preceded and accompanied by brain activities related to the preparation and execution of movement (movement related cortical potentials, MRCP), which have been correlated with the perception of effort (RPE). We combined force measurements, surface electromyography (sEMG), peripheral electrical stimulation (maximal twitch, MT) and MRCP analysis to further our understanding of the neural correlates of peripheral and central changes during a fatiguing task involving the lower limbs. Eighteen healthy volunteers performed 4 blocks of isometric knee extensions at 40% of the maximal voluntary contraction (MVC) for a total of 240 2-s contractions. At the baseline and after each block, we measured RPE, MT and MVC. We simultaneously recorded the force of the knee extensor muscles, root mean square (RMS) of the sEMG of the vastus lateralis muscle, and electroencephalography (EEG) from 64 channels. The MRCPs were extracted from the EEG recordings and averaged in the early (Block 1–2) and late (Block 3–4) blocks. Two cohorts were obtained by cluster analysis based on the RPE (i.e., perception of effort) and MT (i.e., peripheral fatigue). We observed a significant decline in both the MVC (−13%) and RMS (−25%) of the sEMG signal over the course of the task; thus, muscle fatigue had occurred in all of the participants regardless of the cohort. The MRCP amplitude was larger in the fatigued than the non-fatigued MT cohort in the supplementary and premotor areas, whereas the MRCP amplitude was larger in the fatigued than the non-fatigued RPE cohort in the aforementioned areas, and also in the primary motor and prefrontal cortices (PFC). The increase in the positive activity of the PFC, along with the perception of effort, represents a novel result, suggesting that it is modulated more by the perception of effort than peripheral fatigue.